Blind Manipulation of Deformable Objects Based on Force Sensing and Finite Element Modeling - Sanchez, Jose; Mohy El Dine, Kamal; Corrales, Juan Antonio; Bouzgarrou, Belhassen-Chedli; Mezouar, Youcef (Frontiers in Robotics and AI, 2020)
In this paper, we present a novel pipeline to simultaneously estimate and control the deformation of an object using only force sensing and an FEM model. The pipeline is composed of a sensor model, a deformation model and a pose controller. The sensor model computes the contact forces that are used as input to the deformation model which updates the volumetric mesh of a manipulated object. The controller then deforms the object such that a given pose on the mesh reaches a desired pose. The proposed approach is thoroughly evaluated in real experiments using a robot manipulator and a force-torque sensor to show its accuracy in estimating and controlling deformations without the use of vision sensors.